Islamic Eschatological Study on The Dimensions of Pleasure and Suffering in The Grave - Fitriyani, Dina; Al Ayubi, Sholahuddin; Alif, Muhammad (TATHO: International Journal of Islamic Thought and Sciences, 2025)
This study aims to explore in depth the theological and ethical visual dimensions of pleasure and suffering in the grave from the perspective of Prophetic Hadith. Employing a thematic analysis method, this research classifies and examines a set of hadiths related to three major themes: the depiction of the grave, forms of pleasure, and types of suffering experienced after death. The findings reveal that the grave is portrayed as a transitional space with spiritual consequences, including fragrance, tranquility, or torment, as reported in hadiths from Bukhari, Muslim, Tirmidhi, and others. The pleasures of the grave are directly associated with righteous deeds such as reciting the Qur’an, strong faith, and good actions that illuminate the grave. Conversely, suffering is triggered by reprehensible acts, even seemingly minor ones such as excessive weeping or negligence in performing good deeds. Theologically, these hadiths construct a comprehensive eschatological framework of the afterlife. Ethically, they function as moral guidance mechanisms, emphasizing individual accountability for worldly actions. Thus, a profound understanding of the grave based on hadith not only reinforces faith in the unseen but also serves as a powerful ethical motivator in the daily lives of Muslims.